An IxD support model with affective characteristics for dyslexic childrens's reading application - Jamaludin, Zulikha; Husni, Husniza; Aziz, Fakhrul Anuar (2011)
This paper listed affective attributes of an interaction design for a reading application meant for dyslexic children. Different reading styles and unique reading approach of these specific children has long been a challenge for designers to come out with an acceptable interaction design (IxD). Emotional characteristics towards reading such as likes, dislikes, motivation, and satisfaction, which are very much related to affection, are essential in designing the suitable reading application to help them in learning to read and increase their interest in reading. A series of observation and unstructured interviews were conducted involving 28 dyslexic children, whose age range from 7 to 14 years old. The finding reveals that we can combine the affective attributes of the dyslexic children with the interaction model based on Norman’s work to map specific requirements suitable to dyslexic children’s reading ability. This inventive IxD model is proposed for readers with dyslexia. Additionally this paper shows how we translated such model into an automatic reading tutor for special need learners.